Modernisme dan Radikalisme Islam di Indonesia: Menafsirkan Warisan Muhammad 'Abduh dan Rashīd Riḍā - Jajang Jahroni (Studia Islamika, 2004)
Book Review: Giora Eliraz, Islam in Indinesia, Modernism, Radicalism, and the Middle East Dimension, Great Britain: Sussex Academic Press, 2004, xi + 142 pagesOne of theses of this book is that whatever is the movement that emerges in Indeonesian Muslim community, either rationalist or fundamentalist one, it cannot be separated from the one existin the Middle East. The book begins with discussion on modern Islam in Indonesia. it presents discussion several new movements, the concept of the movement; such as the importance of ijtihad, the necessary to left taqlid concept, and various other issues.DOI: 10.15408/sdi.v11i3.599